2001
DOI: 10.1590/s0104-11692001000200004
|View full text |Cite
|
Sign up to set email alerts
|

Diagnósticos de enfermagem em mulheres que freqüentam serviço de planejamento familiar

Abstract: The purpose of this study was to identify nursing diagnoses in women enrolled in a family planning program. An instrument of data collection was elaborated according to the Functional Health Patterns. The sample consisted of 100 adult women. Forty-nine nursing diagnoses, of which 9 with a frequency equal or higher to 45.0% were identified. Further studies are still needed in institutions that offer assistance in the area of family planning in order to examine if the nursing diagnoses found in these women can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
9

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 3 publications
(15 reference statements)
2
2
0
9
Order By: Relevance
“…This investigation revealed use of 63 diagnostic categories, a number that is similar to those described in some of the studies carried out with patients coming from various clinical and surgical units (Barros, 1998; Camiá, Marin, & Barbieri, 2001; Guerriero, Guimarães, & Maria, 2000; Maria, 1997; Soares, Pinelli, & Abrão, 2005; Yom, Chi, & Yoo, 2002). Our ICU admits patients from a variety of types of clinics and surgeries, which may have favored the diversity of the nursing diagnoses identified.…”
Section: Discussionsupporting
confidence: 65%
“…This investigation revealed use of 63 diagnostic categories, a number that is similar to those described in some of the studies carried out with patients coming from various clinical and surgical units (Barros, 1998; Camiá, Marin, & Barbieri, 2001; Guerriero, Guimarães, & Maria, 2000; Maria, 1997; Soares, Pinelli, & Abrão, 2005; Yom, Chi, & Yoo, 2002). Our ICU admits patients from a variety of types of clinics and surgeries, which may have favored the diversity of the nursing diagnoses identified.…”
Section: Discussionsupporting
confidence: 65%
“…The interviewees (3) also reported that the choice of method may be influenced by the income of the client and their availability in the health service, confirming the results of another study (18) . Furthermore, the adaptation of women to the contraceptive can also influence this choice.…”
Section: We Offer Contraceptives According To the Option Of Indivsupporting
confidence: 77%
“…Furthermore, the adaptation of women to the contraceptive can also influence this choice. (19) and may represent a risk for ineffective use of contraceptive methods (18) . The view that the physician knows what is best for the client, ignoring the autonomy of choice of the latter, emerged within the interviewees' statements.…”
Section: We Offer Contraceptives According To the Option Of Indivmentioning
confidence: 99%
“…What family planning is concerned, some studies in this area also demonstrate the presence of this diagnosis, as the client expresses the desire to seek information to promote her health (13,19) .…”
Section: Resultsmentioning
confidence: 99%